Antarctica, 1979–2016 sea ice extent: total versus regional trends, anomalies, and correlation with climatological variables. Issue 24 (17th December 2017) - De Santis, Angela; Maier, Eder; Gomez, Rodrigo; Gonzalez, Inti
ABSTRACT: Antarctica satellite-derived sea ice extents (SIEs) showed a slight increase over the 1979–2010 period, generally attributed to a number of theories, including a combination of changes in atmosphere- and ocean–sea ice interactions. However, almost all authors agreed on the need of further studies based on a longer period of analysis. In this study, a 6 years longer time series (1979-2016) was analysed to calculate total and regional sea ice trends. Those trends were then correlated with three main climatological variables (air temperature, pressure, and wind components). The results showed an increased positive trend of total 1979–2016 SIE (1.6 ± 0.4% decade −1 ) compared to the 1979–2010 period, mostly due to the thermodynamic effect of winds. Remote factors (El Niño–Southern Oscillation and variations in equatorial Pacific and Indian oceans) also contributed to the sea ice increase by causing disturbances in the wind fields. The regional analysis confirmed the great impact of the increased westerly, katabatic and circumpolar winds, but with some differences with respect to the total trend. The increase of wind speed was stronger in the Weddell Sea and Western Pacific Ocean sectors, which corresponded to an increasing of their decadal SIE (from 1.2 ± 1.1% decade −1 to 1.7 ± 0.8% decade −1 and from 0.5 ± 1.5% decade −1 to 1.8 ± 1.2% decade −1, respectively). The Bellingshausen–Amundsen seas sector showed a decrease of its sea ice loss from −5.1 ± 1.6% decade −1 to −2.9 ± 1.4% decade −1, due to the cooling of the air temperature in the Peninsula and the increase of winds. Contrarily, two sectors – Indian Ocean and Ross Sea – showed a reduction in their increasing trends with respect to the 1979–2010 period.